2008
DOI: 10.1194/jlr.d800034-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of pure lipid hydroperoxides

Abstract: Increasing evidence of lipid peroxidation in food deterioration and pathophysiology of diseases have revealed the need for a pure lipid hydroperoxide (LOOH) reference as an authentic standard for quantification and as a compound for biological studies in this field. Generally, LOOH is prepared from photo-or enzymatically oxidized lipids; however, separating LOOH from other oxidation products and preparing pure LOOH is difficult. Early studies showed the usability of reaction between hydroperoxide and vinyl eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 31 publications
(34 reference statements)
0
40
0
Order By: Relevance
“…In the present study, we improved our previously reported PCOOH preparation conditions 16 e.g., reaction between PCOOH and MxP , and produced 30 mg of PCOOH a pure mixture of 13-and 9-hydroperoxyoctadecadienoyl PCOOH isomers from 100 mg of PC without the formation of unknown brown byproducts. The major sn-2 fatty acid of the resultant PCOOH was 13-hydroperoxyoctadecadienoate.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…In the present study, we improved our previously reported PCOOH preparation conditions 16 e.g., reaction between PCOOH and MxP , and produced 30 mg of PCOOH a pure mixture of 13-and 9-hydroperoxyoctadecadienoyl PCOOH isomers from 100 mg of PC without the formation of unknown brown byproducts. The major sn-2 fatty acid of the resultant PCOOH was 13-hydroperoxyoctadecadienoate.…”
Section: Resultsmentioning
confidence: 86%
“…With regard to stability, PCOOMxP was found to be more stable than PCOOH reported in our previous study 16 . We therefore recommend the following: researchers should prepare and store perketal in chloroform at low temperatures e.g., 80 in advance, regenerate PCOOH from PCOOMxP before the experiment e.g., quantitative study , and use the PCOOH as the reference material.…”
Section: Stability Of Pcooh and Perketalmentioning
confidence: 72%
See 3 more Smart Citations